The non-catalytic partial oxidation of methane in a flow tube reactor using indirect induction heating – An experimental and kinetic modelling study. (21st September 2018) - Li, Chao'en; Kuan, Benny; Lee, Woo Jin; Burke, Nick; Patel, Jim
Highlights: Indirect induction heating for the non-catalytic partial oxidation of CH4 . Effects of temperature, stoichiometry, and H2 addition were investigated. Thermal radiation is the dominant mode of heat transfer within the flow domain. Temperature profile was tested and corrected by CFD with reduced mechanism. Kinetic simulations were consistent with experimental results. Abstract: Methane partial oxidation is one way of producing synthesis gas which is the feedstock of Fischer-Tropsch synthesis and methanol synthesis. The high ignition temperature of methane partial oxidation is always a concern to industries and researches, leading to inaccuracies in temperature measurement, reaction model development, and subsequent understanding of reaction mechanisms and the predictive abilities of developed models. A gas-flow reactor system incorporating indirect induction heating was designed and operated for the non-catalytic partial oxidation of CH4 . Experiments of methane partial oxidation diluted by nitrogen were conducted and the effects of temperature (1270–1767 K), stoichiometry (CH4 /O2 = 1–2), and H2 addition were studied. Thermodynamic and kinetic simulations were also performed in this study and compared to the experimental results. Reduced mechanisms were applied in computational fluid dynamics (CFD) simulations to correct the temperature profiles which were adopted in kinetic modelling. Kinetic simulations of the experimental conditions were conducted using reported mechanisms: GRI-Mech 3.0 and the mechanism developed by Glarborg's group. In general the simulated gas-phase compositions at the exit of the reactor and trends for each set of experiments were consistent with the experimental data. The Glarborg mechanism was found to be more accurate in the prediction of the selectivity of C2 hydrocarbons (particularly acetylene) as the Glarborg mechanism contains more pathways for the conversion of C2 H2 into polycyclic aromatic hydrocarbons (PAHs). The combination of CFD modelling and kinetic modelling offset the deviation of temperature measurement and hence provided a sample for high temperature reaction simulation.